Biceps Tenodesis versus Tenotomy in Treatment of Lesions of Long Head of Biceps Brachii in Patients Undergoing Arthroscopic Shoulder Surgery. Issue 7 (21st July 2017) - MacDonald, Peter B.; McRae, Sheila; Stranges, Gregory A.; Old, Jason; Dubberley, James; Mascarenhas, Randhir; Leiter, Jeff; Nassar, Mark; Lapner, Peter
Objectives: To compare subjective patient-reported outcomes and objective clinical results between biceps tenotomy and tenodesis in patients with lesions of the long head of biceps tendon (LHBT). Methods: The study is a prospective, randomized, controlled trial targeting patients +18 years undergoing arthroscopic shoulder surgery to manage a lesion of the LHBT (+/- rotator cuff repair). Patients were excluded if they had previous surgery on their affected shoulder or any other significant medical comorbidity that could alter the effectiveness of the surgical intervention. Patients were allocated intraoperatively to undergo tenodesis or tenotomy via computer randomization once a LHBT lesion was confirmed. The primary outcome measure was the American Shoulder and Elbow Society standardized assessment of shoulder function (ASES). Secondary outcomes included: Western Ontario Rotator Cuff index (WORC), surgery time, patient reported pain and cramping, presence of a cosmetic deformity, elbow flexion and supination strength, and power. Study time points were pre, and 3, 6, 12, and 24 months post-operative. Magnetic resonance imaging (MRI) was conducted at 12-months post-operative. Results: Fifty-six participants were randomly assigned to each group. Table 1 summarizes the results to 12-months post-operative (collection of data to 24-months post-operative is ongoing until 2017). There were no significant differences in ASES score at pre- or post-surgery time points. In addition, no significant differences were found in WORC, surgery time, pain, or cramping. There was one significant difference in strength identified, the ratio of affected versus unaffected elbow flexion strength was greater in the tenodesis group (0.9 (SD=0.2)) versus the tenotomy group (0.8 (SD=0.3)) at 6-months post-operative. Otherwise, there were no differences in strength ratio identified for elbow flexion or supination strength or power at any time point. At 12-months post-surgery, the relative risk of cosmetic deformity in the tenotomy group relative to the tenodesis group based on patient report was 1.36 (p=0.41) with 12 out of 33 patients in the tenotomy group reporting a bulge in their upper arm compared to 8 out of 30 in the tenodesis group. Similar results were found based on clinical evaluation with a relative risk of 1.7 (p=0.36). MRI findings were available on 40 patients at the 12-month post-operative period. Of 23 in the tenodesis group, one was not intact and retracted 18 cm and two were partially torn. Of the 17 in the tenotomy group, none appeared retracted. Conclusion: Arthroscopic treatment of lesions of LHBT, whether tenodesis or tenotomy, was shown to have favourable results. Elbow flexion strength favoured tenodesis at 6-months, but otherwise there were no significant differences between groups. As data continues to be gathered to 24-month post-operative, longer-term benefits and drawbacks of each procedure may become evident. Table 1. Demographies and outcome measures by group. Tenodesis Tenotomy p-value Randomized (Men/Women) 56 (46/10) 56 (43/13) 0.48 Mean (SD) age (yrs) 58.8 (10.6) 56.0 (8.2) 0.13 Total surgery time (mins) 88 (42) 77 (36) 0.33 ASES: Pre 48.1 (17.7) 47.7 (15.8) 0.91 3-months 65.6 (19.1) 61.1 (22.3) 0.29 6-months 75.5 (18.3) 71.6 (23.5) 0.38 12-months 79.6 (20.3) 77.9 (20.2) 0.74 WORC: Pre 34.5 (15.5) 36.5 (13.2) 0.5 3-months 54.9 (20.4) 54.5 (21.0) 0.94 6-months 69.1 (21.3) 62.5 (22.7) 0.16 12-months 75.3 (21.4) 72.6 (22.8) 0.65 Pain: 3-months 5.3 (3.2) 5.9 (3.0) 0.34 6-months 6.6 (2.9) 6.5 (3.6) 0.96 12-months 7.8 (2.6) 7.1 (3.1) 0.31 Cramping: 3-months 7.4 (3.0) 8.1 (2.6) 0.26 6-months 7.7 (2.6) 7.8 (2.9) 0.88 12-months 8.3 (2.4) 7.7 (3.0) 0.4 Elbow flex strength (affected/unaffected ratio): 3-months 0.78 (0.4) 0.79 (0.2) 0.92 6-months 0.90 (0.2) 0.80 (0.3) 0.04* 12-months 0.98 (0.3) 0.90 (0.2) 0.2 Supination strength (affected/unaffected ratio): 3-months 0.88 (0.3) 0.88 (0.3) 0.99 6-months 1.01 (0.2) 0.92 (0.3) 0.25 12-months 1.01 (0.2) 1.03 (0.3) 0.83 Power (affected/unaffected ratio): 3-months 0.53 (0.3) 0.55 (0.2) 0.72 6-months 0.78 (0.4) 0.72 (0.3) 0.42 12-months 0.81 (0.3) 0.74 (0.3) 0.33 *Significant at p<0.05.